A school educational intervention based on a serious game to promote a healthy lifestyle - Daniela Marchetti§; Federica Fraticelli§; Francesco Polcini; Mario Fulcheri; Angelika Anna Mohn; Ester Vitacolonna (Mediterranean Journal of Clinical Psychology, 2018)
Background: Maintaining a healthy lifestyle is a basic aspect of well-being. Since public health surveillance systems underlie high prevalence of obesity and diet-related ill health, efforts to provide effective intervention to prevent these conditions are of primary importance. The present study aims to test and validate a school intervention based on a serious game (SG) directed to empower a healthy lifestyle in children, actively involving their parents and teachers.